Effect of oral injection of tramadol, sildenafil and combined of tramadol and sildenafil on serum testosterone level for Wistar breed male rats - Farag, Rabie Said; El Nawawy, Mohamed Abdel; Fathy, Wael Mohamed; Atiaa, Hamada (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Introduction:Testosterone is the main sexual hormone in human males, and has a pharmacological effect on the physiology of sexual function. It is known that suppression of testosterone in eugonadal adult males leads to reduced sexual desire and activity, and may result in erectile dysfunction. Tramadol is rapidly and almost completely absorbed after oral administration but its absolute bioavailability is only 65–70% due to first-pass metabolism. Sildenafil citrate is a water soluble citrate salt that was firstly synthesized by Pfizer in United Kingdom to treat hypertension and angina pectoris. Interestingly, this drug exhibited a different pharmacological effect, a marked penile erection, and became the first-line treatment option to erectile dysfunction. Aim of the work :the main work goal of this search was to measure and compare between mean serum testosterone concentrations after oral injection of tramadol, sildenafil , and combination of tramadol and sildenafil beside healthy subjects.Investigated Parameter: quantitative analysis of Free Testosterone ELISA Kit in serum by The Calbiotech, Inc. 10461 Austin Dr, Spring Valley, CA U.S.A., depending on McCann, D., et al 1985.Results In the present study, the results of GT group revealed that administration of tramadol 50 mg /Kg/day for 10, 20 days and 30 days indicated that the measured testosterone levels were lower than the (GC) control group, and the decrease in testosterone mean concentrations in GT3, than GT2, than GT1. In our research GS group administration of sildenafil 50 mg /Kg/day for 10, 20 and 30 days groups indicated that increase testosterone levels than that in control GC group, and there was an increase in testosterone mean concentrations in GS3, than GS2, than GS1. The present study reveled in GT&S administration of tramadol 50 mg /Kg/day combined with sildenafil 50 mg /Kg/day that the mean serum testosterone concentrations in (GT&S1), (GT&S2) and (GT&S3), were decrease than in the mean serum testosterone concentrations (GC), but this decrease in the mean serum testosterone concentrations in (GT&S1), (GT&S2) and (GT&S3), were quite higher than mean serum testosterone concentrations in GT1, GT2, and GT3, also and there were a decrease in mean testosterone mean concentrations in (GT&S3) than that in (GT&S2) and (GT&S1)conclusion: tramadol administration decrease testosterone levels, while sildenafil increase testosterone levels, while the combination between tramadol & sildenafil decrease testosterone levels.